Perspective on Inheritance Rights in Other Wives - Fawwaz Rohmanna, Lidya; Adebayo, Adesoji Kolawole; Alam, Syamsul (Manunggal Halim Jaya, 2023)
This research aims to investigate and understand the position of wives who marry consecutively and who are not the first wife in the perspective of heirs according to the Compilation of Islamic Law. The research method used is normative-juridical. Analysis of the research results shows that the position of other wives in polygamous marriages is equal in rights to the first wife. Joint property in a polygamous marriage is divided fairly, where the legal consequences of the inheritance of a husband who marries more than once legally are that when the husband dies, the division of joint property in his marriage is half of the joint property obtained with the first wife, and half of the joint property obtained with the second wife, each separately without any mixing of assets. Each wife in a polygamous marriage has the right to her husband's inheritance. The conclusion of this study is that there is no difference in inheritance rights between the first wife and subsequent wives, in accordance with the provisions of Religion and the Compilation of Islamic Law applicable in Indonesia. Recommendations from this research include the need for reform in the Law and incorporated in the omnibus rule of law, especially related to the distribution of inheritance in polygamous marriages, as some laws have accommodated what is implied in the Qur'an and AlHadith. The terms in the law need to be adjusted to reflect fair and balanced principles in accordance with religious values. In addition, wives in polygamous marriages need to pay attention to factors that may limit their inheritance rights and follow religious recommendations.